Wave Transmission Analysis of Timoshenko Beam Junction with Mindlin Plates Connected in the Same Plane - Young-Ho Park (한국해양공학회지)
Energy flow analysis (EFA) models that account for significant shear deformation and the rotatory inertia effects in out-of-plane motion are essential for performing reliable EFA of practical composite structures, such as large ships or offshore platforms. The power coefficients for transmitted and reflected waves caused by incident waves at arbitrary angles in the incident Mindlin plate were derived by analyzing the displacement fields of semi-infinite Mindlin plates and an infinite Timoshenko beam. This enables the determination of the power transmission and reflection coefficients for diffuse fields, which are crucial for calculating the frequency-averaged vibrational power transfer relationship among coupled finite structures. The power transfer relationship, derived from the undamped wave solutions of the Mindlin plate and the Timoshenko beam, showed through numerical examples that the stiffening Timoshenko beam effectively insulates the Mindlin plate from out-of-plane vibrational power. Numerical analysis showed that the stiffening beam effectively blocks the vibrational power transmission of out-of-plane waves in the incident Mindlin plate. In addition, the power transmission and reflection tendencies of these waves vary with the cross-sectional size of the stiffening Timoshenko beam. This approach aims to enhance the reliability of vibrational analysis for stiffened plate structures.